Medical termination of a partial hydatidiform mole with coexisting fetus during second trimester; management dilemma: a case report - Behura, Jharna; Paul, Mohini; Seth, Ankit; Naaz, Aafreen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Partial hydatidiform mole and coexisting foetus is a rare condition, with an incidence of 122,000-1,000,000 pregnancies. It presents a dilemma for obstetricians when detected in second trimester of pregnancy. Medical termination is effective during second trimester; however, it increases the risk of occurrence of persistent trophoblastic disease. Following a review of literature, it was seen that most of the PHMCF terminated by medical induction during second trimester resulted in the development of PTD and lung metastasis. However, cases terminated by caesarean section during the third trimester did not develop PTD or metastasis. A 34 year old woman, gravida 3 para 2 at 25 weeks and 3 days of gestation, presented with absent fetal movements. She was markedly pale. She had no prior antenatal visits. Ultrasound examination revealed a single intrauterine foetus at 23 weeks of gestation with no cardiac activity. Spalding sign was positive. Liquor was reduced and showed internal echoes, secondary to intramniotic bleed. Placenta was grossly enlarged, anterior in location with multiple cystic areas suggestive of a partial mole. As her haemoglobin was 5.6 grams, she was transfused with 3 units of packed cells. The patient underwent induced medical abortion after counselling for risk of persistent trophoblastic disease and long term follow up. She was followed up with weekly serial serum beta hCG monitoring, which returned to normal within a month. She showed no signs of persistent trophoblastic disease at 3 months follow up and has been advised to continue follow up for a year. Mid-trimester termination of pregnancy due to PHMCF is challenging due to high risk of PTD and metastasis associated with it. Performance of caesarean section is not recommended during second trimester of pregnancy but is a relatively safer strategy to avoid the risks of persistent trophoblastic disease.